Behavioural Economics Driven Entrepreneurship Nudges Among Individuals - GARUS, Maria; FLAK, Olaf; KOZUSZNIK, Barbara; SÁNCHEZ, Virginia Barba (Theoretical and Practical Research in Economic Fields, 2025)
This study aimed to develop and implement strategies rooted in the principles of behavioural economics to foster the growth of entrepreneurship within higher education institutions. By focusing on technology transfer offices (TTOs) as critical facilitators of innovation and entrepreneurship, the research assessed the competencies of 40 TTO employees from seven different countries. Utilizing the 180-degree feedback method, which incorporates both self-assessments and peer evaluations, the study identified significant discrepancies between how TTO employees perceived their skills and how their peers evaluated them. Notably, areas such as innovativeness, creativity, and collaboration showed marked differences, indicating a potential misalignment in self-awareness and actual competency levels. The findings emphasized the necessity for a more balanced and holistic approach to competency development, ensuring that TTO employees are equipped not only with technical skills but also with interpersonal and innovative capabilities essential for fostering an entrepreneurial mindset. In addition to the competency assessment, the study included feedback from 203 participants who attended entrepreneurship workshops facilitated by TTO employees involved in an international project. The participants overwhelmingly rated the training as useful and practical, suggesting that such initiatives significantly contribute to entrepreneurial skill development. Ultimately, this research highlights that enhancing the competencies of TTO employees is crucial for providing better support for academic entrepreneurship. As TTO employees become more adept in their roles, this leads to increased readiness among faculty and students to undertake business ventures, thereby contributing to a vibrant entrepreneurial ecosystem within higher education institutions. The study calls for ongoing professional development and training programs for TTO staff to ensure they remain effective in their support roles, ultimately fostering a culture of innovation and entrepreneurship in academia.